Our Experience of Ponseti Treatment for Clubfoot Deformity at District Head Quarter Hospital Timergara, Khyber Pakhtunkhwa (Journal of Pakistan Orthopaedic Association, 2020)
Objective: To determine the outcome of Ponseti treatment for clubfoot(Congenital Talipes Equino Varus) deformity in neonates.Methods: It was a descriptive study conducted in District Head Quarter Hospital Timergara Khyber Pakhtunkhwa from 25th July 2017 to 25th August 2018. All children below one year of age with Congenital Talipes Equino Varus(CTEV) deformity meeting the inclusion criteria were included in our study. The pretreatment severity of clubfoot deformity was scored through Pirani Scoring system. All the children were then subjected to manipulation and weekly serial casting by Ponseti technique and the final outcome was assessed by improvements in the Pirani score and graded as excellent, good and poor.Results: In our study the total clubfeet were 48 in 32 neonates. Mean age was 4.3 months(range 2.5 to 11 months) Male children were 22(68.7%) and female 10(31.2%).Bilateral clubfeet were present in 20(62.5% ) children while unilateral in 8(25%).The pre-treatment mean Pirani score was 5.5 while post treatment mean score was less than 0.5.Excellent and good outcome was achieved 46( 95.8%)and 2( 4.1%) feet respectively.Conclusion: Ponseti treatment for Congenital Talipes Equino Varus deformity in neonates produced excellent outcome in majority of patients. The Ponseti technique of serial casting should be the treatment of choice to treat congenital clubfoot deformity.